Basic Constitutive Equations in Elasto-Plasticity – A Review - Aliyu, O. H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The present paper reviews the constitutive equations of engineering materials in the elasto-plastic regime. Here the plastic flow rules, strain rate, yield function, overstress function as well as evolution equations for the internal parameters are discussed. Similarly, the implementation of the elasto-viscoplastic constitutive model in a standard finite element code is also discussed and it has been concluded that an appropriate choice of material model is key in accurately simulating the behaviour of an engineering material to applied loading. It is also recommended that the appropriateness of the selected constitutive response is crucial for mimicking precise the material behaviour.